Open Access and the Humanities : Contexts, Controversies and the Future - Eve, Martin Paul (Cambridge : Cambridge University Press, 2014)
If you work in a university, you are almost certain to have heard the term'open access' in the past couple of years. You may also have heard either that it is the utopian answer to all the problems of research dissemination or perhaps that it marks the beginning of an apocalyptic new era of'pay-to-say' publishing. In this book, Martin Paul Eve sets out the histories, contexts and controversies for open access, specifically in the humanities. Broaching practical elements alongside economic histories, open licensing, monographs and funder policies, this book is a must-read for both those new to ideas about open-access scholarly communications and those with an already keen interest in the latest developments for the humanities. This title is also available as Open Access via Cambridge Books Online.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Open Access title.